The Right to Rest and Disconnect in the Slovenian Legal System – A Legal Reform in the Making - Iza Beširević (LeXonomica, 2024)
The author discusses the legal aspects of the regulation of the right to daily and weekly rest and right to disconnect. The primary focus is on the study of Slovenian normative legal framework (with an emphasis on the amendment to the Employment Relationships Act, through which Slovenia regulated the right to disconnect). The measures to ensure the right to disconnect that employers must adopt (until 16th November 2024) should be, if possible, established through the collective agreement at the sector level. However, if a collective agreement with relevant content is not concluded, employers will have to adopt the measures themselves in their general acts. Following the review of sector collective agreements in the Republic of Slovenia (in September 2024), the author concludes that most collective agreements do not yet regulate the right to disconnect, and those that do, lack the necessary measures. Therefore, the inclusion of the right to disconnect at the statutory level has, so far, not resulted in any amendments to collective agreements regarding the right to disconnect. It should be noted that further research (of this kind) will have to be carried out in the forthcoming period in order to fully assess the impact of the legal reform in question.PovzetekAvtorica obravnava pravne vidike urejanja pravice do dnevnega in tedenskega počitka ter pravice do odklopa. Pri tem se osredotoča predvsem na normativni okvir slovenskega pravnega reda (s poudarkom na obravnavi novele Zakona o delovnih razmerjih (ZDR-1D), s katero je bila v Sloveniji uvedena pravica do odklopa). Ukrepi za zagotavljanje pravice do odklopa, ki jih morajo sprejeti delodajalci (do 16. novembra 2024), naj bodo, če je to mogoče, določeni v kolektivni pogodbi na ravni dejavnosti. Vendar pa, če do sklenitve kolektivne pogodbe z relevantno vsebino ne pride, bodo morali delodajalci ukrepe sprejeti sami v svojih splošnih aktih. Po pregledu kolektivnih pogodb na ravni dejavnosti v Republiki Sloveniji (v septembru 2024), avtorica ugotavlja, da večina veljavnih kolektivnih pogodb še ne ureja pravice do odklopa, tiste, ki jo urejajo, pa ne določajo ukrepov. Torej, vključitev pravice do odklopa na zakonsko raven do sedaj ni privedla do sprememb kolektivnih pogodb glede ureditve pravice do odklopa. Ob tem je treba izpostaviti, da bo za celovito oceno učinkov predmetnih zakonskih sprememb treba izvesti nadaljnje (tovrstne) raziskave še v prihajajočem časovnem obdobju.